1999
DOI: 10.1080/00332747.1999.11024850
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Psychopathology in Schizophrenia: The Association between Personality Traits and Symptoms

Abstract: Research has indicated that stable individual differences in personality exist among persons with schizophrenia, and that they likely predate the onset of illness. Little is known, however, about whether individual differences in personality are related to levels of psychopathology. This study tested the hypotheses that levels of Extroversion, Neuroticism, and Psychoticism are associated with symptomatology. Accordingly, measures of these dimensions of personality and of symptomatology were obtained simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 41 publications
10
57
0
1
Order By: Relevance
“…Lysaker et al 28 point out that stable individual differences in personality exist among persons with schizophrenia. It may be speculated whether such personality differences may be linked with dopamine receptor variants.…”
Section: Discussionmentioning
confidence: 99%
“…Lysaker et al 28 point out that stable individual differences in personality exist among persons with schizophrenia. It may be speculated whether such personality differences may be linked with dopamine receptor variants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an association between personality and psychosis [29][30][31][32][33] . However, one major shortcoming with these studies is that they have included 'psychosis' or 'schizophrenia' and did not examine specifi c aspects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been linked to higher levels of disability (Herran et al, 2006) and passive and avoidant coping strategies (Lysaker et al, 1999). There is also some evidence to suggest that N may possibly be related to emotional discomfort symptoms (Lysaker et al, 1999;Lysaker& Taylor, 2007). High levels of E have been associated with higher QoL ratings , lower negative symptoms Lysaker et al, 1999), and lower emotional discomfort symptoms (Lysaker et al, 1999;Lysaker& Taylor, 2007).…”
Section: Horan and Colleagues (2005) Also Suggested A Link Between Pementioning
confidence: 98%
“…There is also some evidence to suggest that N may possibly be related to emotional discomfort symptoms (Lysaker et al, 1999;Lysaker& Taylor, 2007). High levels of E have been associated with higher QoL ratings , lower negative symptoms Lysaker et al, 1999), and lower emotional discomfort symptoms (Lysaker et al, 1999;Lysaker& Taylor, 2007). In one study high extraversion was found to predict better social functioning as well as increased social support seeking , but also poorer work performance (Lysaker et al, 1998).…”
Section: Horan and Colleagues (2005) Also Suggested A Link Between Pementioning
confidence: 99%
See 1 more Smart Citation